The Correlation between Students’ Watching English Animation Movie Habit with Their Vocabulary Mastery - Ni Kadek Sugi Juniari; Putu Ayu Paramita Dharmayanti; Anak Agung Putu Arsana (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
The study aims at figuring out the correlation between students’ watching English Animation Movie habit with the vocabulary mastery of the eleventh - grade students of SMAN 1 Sukawati in Academic Year 2020/2021. In the present study, the researcher specified the type of movie into animation movie which individual’s drawings, paintings, or illustrations are photographed frame by frame (stop-frame cinematography). The undertaking of the research was mainly based on the preliminary study. The subjects were the eleventh - grade students of SMAN 1 Sukawati in academic year 2020/2021. There were 60 subjects which came from 12 classes. The design was ex-post facto correlational research design. The research was carried out by distributing a questionnaire about students’ habit in watching English animation movies and a vocabulary test through google form. The result showed that there was significant correlation between students’ watching English Animation Movie habit with the vocabulary mastery of the eleventh - grade students of SMAN 1 Sukawati in Academic Year 2020/2021 with the correlation value was 0.719 that belonged to high correlation scale (0.600-0.800).  In short, the study showed higher score that the students got in the questionnaire the higher score of vocabulary test that achieved.